Analysis of the dynamics of occupational morbidity and its consequences in Ukraine in comparison with other countries of the world - M.H. Prodanchuk; A.V. Basanets; O.P. Kravchuk; K.Y. Hashynova; V.A. Hvozdetskyy (Medičnì Perspektivi)
In general, 5-7% of global deaths are related to occupational diseases and industrial injuries. The social expenses related to occupational diseases reach 2-14% of the gross national product (GNP) in different countries. The aim of the investigation is to analyze the indicators and dynamics of occupational morbidity, related incapacity for work and disability in Ukraine in comparison with other countries of the world. The analysis of reporting materials of the State Labor Service of Ukraine, reports of the World Health Organization, and the International Labor Organization was carried out. According to the State Statistics Committee of Ukraine, the number of people working in the main sectors of the economy in conditions that do not meet sanitary and hygienic standards and requirements is 836,600 people, or 28.4% of the registered number of full-time employees. The results obtained in the study indicate the discrepancy of statistical data on occupational morbidity and its consequences with the real situation: the level of occupational morbidity in Ukraine is 17 times lower than the European average, despite the fact that the working conditions in most of them do not meet hygienic standards. The most common occupational diseases in Ukraine are diseases caused by dust exposure: pneumoconiosis, chronic bronchitis, COPD, which make up 39% of the occupational morbidity structure. The global indicator of Disability Adjusted Life Year (DALYs) from the occupational exposure factors in the world (5.1%) is 3 times higher than the similar one in Ukraine (1.53%). The rate of Years lived with disability (YLDs) caused by occupatipnal factors in Ukraine is 0.38 per 100,000 population, and is significantly lower than the similar rate in most European countries and the USA as well. Obvious distortion of statistical indicators on occupational morbidity and related consequences leads to inconsistency in determining priority areas of health care activity. Due to the process of reintegration of Ukraine into the European Union, the requirements for sanitary and hygienic working conditions, medical and sanitary services for workers, the system of recognition, registration and prevention of occupational diseases should definitely be adapted to international requirements and recommendations as well.